Loss of pulsatile luteinising hormone secretion in men with chronic renal failure. Issue 6509 (7th December 1985) - Rodger, R S; Morrison, L; Dewar, J H; Wilkinson, R; Ward, M K; Kerr, D N
Abstract : In an attempt to determine the nature of hypothalamic and pituitary dysfunction in renal failure the secretory patterns of luteinising hormone were measured in men with end stage renal disease and compared with those in healthy controls and renal transplant recipients of similar age distribution. Mean luteinising hormone and oestradiol concentrations were significantly higher and the number of luteinising hormone secretory pulses was significantly lower in uraemic men compared with controls. Plasma testosterone and oestradiol concentrations were significantly lower in renal transplant recipients than normal men, but there were no significant differences in mean gonadotropin concentrations or the number of pulses of luteinising hormone between the two groups. As pulses of luteinising hormone are thought to reflect episodic gonadotropin releasing hormone from the hypothalamus these data suggest that uraemia interferes with central mechanisms controlling synchronised release of gonadotropin releasing hormone. This defect appears to be reversible after successful transplantation.